If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 3y + 13 = 23 Reorder the terms: 13 + 2y + 3y = 23 Combine like terms: 2y + 3y = 5y 13 + 5y = 23 Solving 13 + 5y = 23 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 5y = 23 + -13 Combine like terms: 13 + -13 = 0 0 + 5y = 23 + -13 5y = 23 + -13 Combine like terms: 23 + -13 = 10 5y = 10 Divide each side by '5'. y = 2 Simplifying y = 2
| -16=-6-5z | | h(t)=-16t^2+192t+90 | | 27+35+23=180 | | 2z-13=27 | | -40=-5pm | | 23-3w=80 | | 240x^3+540x^2-2160x=0 | | 8x-22=3(3x+21)-x | | 1492=75 | | -7x-66=-2x+54 | | 7a-2=40 | | .8x+5=0.2(40+x) | | 4ln5/1-ln5 | | 42=3x+6 | | 240x^2+675x-2160=0 | | (4x+5)+x=360 | | X/6-1=-6 | | (4x+5)+c=360 | | 4x/x=30 | | -5(6x-2+6)=30 | | (4x+5)+x=180 | | 3(x-5)-2(2x+1)=-8 | | l+15.2=-4.2 | | x^3+x^2-125d^3-25d^2= | | 240x^3+675x^2-2160x=0 | | -12x-141=-3x+102 | | 5*2-8*3+9= | | 10-4y=20 | | 4x-4y=y^2 | | -101-x=12x+55 | | -(y-90)= | | f(n)=5y+4x |